2020
DOI: 10.1159/000505670
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Vascular Smooth Muscle Calcium Sensitivity and Loss of Endothelial Vasodilator Influence Contribute to Myogenic Tone Development in Rat Radial Uterine Arteries during Gestation

Abstract: Uterine artery myogenic tone (MT) develops during pregnancy in hemochorial placentates such as rats and humans. The physiological reason for its appearance is not clear, and we reasoned that it may be a late pregnancy (LP) event in preparation for controlling hemorrhage during parturition. We also hypothesized that gestational increases in RhoAinduced vascular smooth muscle (VSM) calcium sensitivity are contributory and occur under the tonic influence of nitric oxide (NO). Second-order pre-placental radial art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Although L-NAME is commonly directly applied to vessels in ex vivo studies (used for over 20 yr ( 76 )), few studies have explored the effect of administering L-NAME in vivo on vascular reactivity. One study showed that L-NAME administration impaired acetylcholine induced vasorelaxation in rat aortic rings ( 77 ) and another that L-NAME impaired myogenic tone of rat uterine radial arteries ( 78 ). However, it is understood that vascular adaptations in pregnancy are distinct between rats and mice ( 79 ), which may explain the discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although L-NAME is commonly directly applied to vessels in ex vivo studies (used for over 20 yr ( 76 )), few studies have explored the effect of administering L-NAME in vivo on vascular reactivity. One study showed that L-NAME administration impaired acetylcholine induced vasorelaxation in rat aortic rings ( 77 ) and another that L-NAME impaired myogenic tone of rat uterine radial arteries ( 78 ). However, it is understood that vascular adaptations in pregnancy are distinct between rats and mice ( 79 ), which may explain the discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Myogenic tone is an intrinsic property of the vascular smooth muscle cells that enables them to constrict in response to an increase in perfusion pressure [58], maintaining blood flow in high perfusion organs, such as the pregnant uterus [59,60]. Pregnancy-induced changes in myogenic tone of uterine arteries are species-dependent and involve different intracellular mechanisms.…”
Section: Myogenic Tone and Flow-mediated Vasoreactivity In Uterine Ar...mentioning
confidence: 99%
“…Similar to human myometrial arteries from late pregnant women, preplacental uterine radial arteries from late pregnant rats (Gestational Day 20, term = 21–22 days) showed greater myogenic tone than arteries from rats at mid‐gestation (Gestational Day 12). NOS inhibition significantly enhanced pressure‐dependent tone only in arteries from early pregnant (Gestational Day 12) but not from late pregnant (Gestational Day 20) rats [60]. In addition, uterine arteries from late pregnant rats had increased RhoA kinase expression [60] and a significant elevation of intracellular Ca 2+ ([Ca 2+ ] i ) [59].…”
Section: Uterine Circulatory Adaptations To Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…The myogenic tone thus functions as an autoregulatory process to maintain constant blood flow to critical organs across varying blood pressures [ 9 ]. The myogenic tone was reported to be increased (human myometrial arteries and rat radial uterine arteries [ 10 , 11 , 12 , 13 , 14 , 15 ]) or decreased (mouse and guinea pig main uterine arteries [ 16 , 17 , 18 ]) with pregnancy. In addition to vascular function, the structure of arteries also determines their capacity for blood flow.…”
Section: Introductionmentioning
confidence: 99%